Evaluation Of Communication Strategy Of Waste Management Program Using AIDDA Model (Awareness, Interest, Desire, Decision, Action) Environmental Communication Sociology Approach - Tyas Novita Herawati; Lina Saptaria; Edwin Agus Buniarto; Bambang Suwarsono; Novita Rifaul Kirom (Jurnal Mamangan, 2023)
Evaluation of communication strategies is very important to measure the success and follow-up of waste management programs by the Environmental Service (DLH) of Kediri Regency. The previous communication strategy evaluation model was considered ineffective and did not provide comprehensive information. This study aims to apply the AIDDA model ( Attention, Interest, Desire, Decision, Action ) in waste management program evaluation activities in Kediri Regency based on the theory of environmental communication sociology. Researchers examine the comparison of communication strategy evaluation results before and after using the AIDDA model. In addition, assess community involvement and identify factors that influence the success of this model. The research method is descriptive qualitative with a case study approach. Data collection techniques use interviews, observations, and documentation. The number of informants in this study was 6 people, namely 3 staff of the DLH PSLB3 division and 5 waste managers in five villages in Kediri Regency. The results of the study found that the evaluation of the AIDDA model communication strategy can ensure the effectiveness of communication, increase community participation, optimize resource use, improve program sustainability, and provide empirical evidence of the effectiveness of communication strategies. The results of this study can provide valuable information for DLH and stakeholders to design more effective communication strategy evaluations in waste management programs, environmental responsibility programs and sustainability support according to needs.